Impact of Recreational Swimming on Physical Condition of the Visually Impaired Junior Pupils - Tetiana Tsyupak; Yurii Tsyupak; Feliks Filak (Lesya Ukrainka Volyn National University, 2017)
In the article the comparative analysis of physical development and physical preparedness of visually impaired schoolchildren of junior age comes true after application of the health swimming and his influence on the bodilycondition of children. An important problem in the period of development of th functional systems of organism is strengthening of health of children of midchildhood, as general bases of health aremortgaged exactly in this period of life, that it is especially important for children that have defects of sight, as at themarked pathology functional possibilities of organism andlevel of capacity below, than in healthy. Basic motions provide the health of children, them normal development and physical perfection. A correction and in demnification of lacks of physical development and physical preparedness of visually impaired children ade quately influenced the health swimming on the bodily condition of children, to what indexes testify got during an experiment. Onquestioning of parents and teachers, application of th health swimming influenced also on reduction of catarrhal diseases among children, that was marked on the visit of school lessons. The results of our researches testify to the necessity of application of the health swimming, that must take the important place in the complex of measures on the aim of strengthening of health of children, improvement of motiveinternalss, prophylaxis of secondary diseases of visually impaired students of midchildhood.